Survey on depth perception in head mounted displays: distance estimation in virtual reality, augmented reality, and mixed reality. Issue 5 (21st March 2019) - El Jamiy, Fatima; Marsh, Ronald
Abstract : Depth perception is one of the important elements in virtual reality (VR). The perceived depth is influenced by the head mounted displays that inevitability decreases the virtual content's depth perception. While several questions within this area are still under research; the main objective of this study is to survey the recently conducted studies on depth perception in VR, augmented reality (AR), and mixed reality (MR). First, depth perception in the human visual system is discussed including the different visual cues involved in depth perception. Second, research performed to understand and confirm depth perception issue is examined. The contributions made to improve depth perception and specifically distance perception will be discussed with their main proposed design key, advantages, and limitations. Most of the contributions were based on using one or two depth cues to improve depth perception in VR, AR, and MR.